Physical activity and long-term quality of life among colorectal cancer survivors: a population-based prospective study - Eyl-Armbruster, Ruth Elisa; Koch, Lena; Jansen, Lina; Walter, Viola; Carr, Prudence R.; Hoffmeister, Michael; Chang-Claude, Jenny; Brenner, Hermann; Arndt, Volker (Cancer Prevention Research, 2020)
Evidence suggests that physical activity(PA) is positively associated with health-related quality of life(QOL) in colorectal cancer(CRC) survivors. However, little is known regarding long-term effects of PA on QOL and if pre-diagnosis PA is associated with QOL in the years after diagnosis. Our study aimed to investigate the association of pre- and post-diagnosis PA with long-term QOL in CRC survivors. This study is based on a population-based cohort from Germany of 1781 newly diagnosed CRC survivors over a five-year period. Physical activity was assessed at diagnosis and at five-year follow up(5YFU). Quality of life was assessed by the EORTC Quality of Life Questionnaire-Core 30 at 5YFU. Multivariable linear regression was used to explore associations between pre- and post-diagnosis PA and QOL. No evidence of a positive association between higher levels of pre-diagnosis PA and better long-term QOL was found. Higher levels of pre-diagnosis work-related PA and vigorous PA were even associated with decreased QOL in domains such as cognitive (Beta(ß)= -2.52, 95% confidence interval(CI)=−3.77,-1.27; ß=-1.92, CI=-3.17,-0.67) and emotional functioning (ß=-2.52, CI=−3.84,-1.19; ß=-2.12, CI=-3.44,-0.80). In cross-sectional analyses, higher post-diagnosis PA was strongly associated with higher QOL. Survivors physically active at both pre- and post-diagnosis as well as survivors who increased their PA between pre- and post-diagnosis reported significantly higher long-term QOL compared to survivors who remained inactive at pre- and post-diagnosis. In this study, higher pre-diagnosis PA does not appear to be associated with higher QOL among long-term CRC survivors but our results support the importance of ongoing PA throughout survivorship.